Distribución de los pterópodos (Gastropoda: Thecosomata y Pseudothecosomata) del Golfo de México y zonas adyacentes - Suárez M., Eduardo (Revista de Biología Tropical, 1994)
A checklist of 51 pteropod species and lower taxa has been compiled from the literature about pteropod moUuscs throughout the Gulf of Mexico, the Florida Current and the Caribbean Sea, and from field observations. Bathymetric distribution, biogeographic and ecologic affinities and zoogeographic records are presented for each species. The pteropod fauna of the Gulf of Mexico -Caribbean Sea area is mainly tropical, inhabits surface waters and has elements Gommon to both neritic and oceanic zones. Considering all the species reported in the Northwestern Tropical Atlantic, only 62% have been coUected from the southern Gulf of Mexico, which reflects the paucity of studies in this zone and a possible undersampling of the group in subsurface strata, below 2 00m.